(untitled) (International Journal of Ayurveda and Pharma Research, 2019)
Introduction: ‘Mutraghata’ can be equated with group of obstructive uropathic disorders. As explained in Sushrutha Samhitha, it is of 12 types and ‘Vatasthila’ is one among them, which is closely similar to Benign Prostatic Hyperplasia. BPH is a progressive disease of advancing age. Histologically the inner zone of the periurethral gland undergoes hypertrophy and an adenoma is formed. Usually men around 60 years, suffer from mild, moderate and severe grade of BPH. Objectives: To evaluate the efficacy of Gokshura kwatha in the management of Mutragatha/ B.P.H. and to improve quality of life of BPH sufferer. Method: It is a single blind, clinical study on diagnosed cases of B.P.H, Gokshura kwatha was given for 60 days (20ml BD) with Sita and honey with follow-up of 4 months. Changes in subjective criteria (by IPSS Index) and objective criteria (by USG) were recorded before and after treatment. Result: Gokshurakwatha shown more significant relief on associated symptoms of Mutraghata including, burning sensation, painful micturition, pus and blood discharge etc. Interpretation: On the basis of the beneficial effects of Gokshura kwatha churna, it can be opined that it gives good result symptomatically. Conclusion: The subjective features were relieved significantly. But observed, no much difference in the objective criteria. The effect of Gokshurakwatha on the straining significantly reduced, prostate size has not reduced significantly. As for follow up period, relief of symptoms observed to be sustained up to one month in majority of patients.